Design of tunnel drier for the non-centrifugal sugar industry. (14th October 2020) - Raj, S P; Srinivas, M; Sravya, B; O'Donovan, T S; Reddy, K S
Abstract: The quality and shelf-life of NCS (non-centrifugal sugar) mainly depend on the moisture content present in it. NCS formed by the current practice of open sun drying contains moisture substantially greater than the acceptable level of 3%. This paper presents the work undertaken to design a tunnel dryer to achieve the required moisture content of granular NCS for various load conditions. An experimental investigation was conducted on a laboratory-scale dryer to achieve the required moisture content for various loads. This experimental data was compared with the output of two drying models and a validated one that could be used to design an industrial-scale dryer. For various load conditions on each tray and dryer exit temperature, nine different cases were determined. The number of trucks, drying time, and energy requirements were computed using the validated theoretical model. A tunnel dryer with a length, height and width of 18, 1.2 and 1 m respectively and 18 trucks with 24 trays on each truck is shown to be dry 1 tone of NCS based on the minimum energy requirement of 176.49 MJ, and a drying time of 68 min.